IMPLEMENTASI MODEL DISCOVERY LEARNING PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMAN 8 MALANG - Siti Mukaromah; Rosichin Mansur; Muhammad Sulistiono (VICRATINA, 2021)
The implementation of the discovery learning model on the learning motivation of students in learning Islamic education and character at SMAN 8 Malang. This research used a qualitative approach, and type of research used case study. In data collection technique, researcher used several techniques there are observation, interviews and documentation. Meanwhile, in data analyzing, the researcher used data collection technique, data condensation, data presentation, and conclusions. To check the validity of the data, researcher used two kinds of triangulation, there are source triangulation and method triangulation. The presented of researcher at the research has an important influence in obtaining information or data in as much detail as possible. From the results of the study it was found that: (1) The implementation of the discovery learning model on the learning motivation of students in learning Islamic Education and character at SMAN 8 Malang. By using the discovery learning model, it changed students' views of Islamic subjects which were initially monotonous and boring to become fun, interesting and varied, so that students' learning motivation was increasing, it was marked by active and creative students in following the learning process. The implementation of the discovery learning model consists of 3 activities, (a) Pre-Learning includes making syllabus and lesson plans (b) The learning process is a core activity in a learning using a certain time duration (c) authentic assessment. Kata kunci : Implementation, discovery learning model, Islamic education.